Project Based Learning For Brush Less DC Motor - Ihatiari Prastyaningrum; Pramudya Ardi (Universitas Sebelas Maret, 2020)
Abstract: The rapid development of technology demands that the younger generation be more creative and innovative to develop themselves. As we know, the current supply of fossil fuels is running low, and of course this is a challenge for the younger generation. Facing this, there are currently many electric-based motorized vehicles being developed which hope that in the future they will be able to develop and have wider utilization. One of the choices is an electric motor. In order to support the development of electric vehicles, the Electrical Engineering Education Study Program of the PGRI Madiun University, is trying to develop an electric motor based on a BLDC motor or Brushless DC Motor. Where understanding the concept first emphasized so that students better understand the work system of this motor BLDC. Through project-based learning, students can understand more quickly about the BLDC motor work system. The results showed an increase in understanding of the concept of the work system of BLDC MOTOR. The boost has a medium N-Gain value. From these results, it can be concluded that through project-based learning for BLDC motors, it can improve understanding of the concept of the BLDC motor work system.Abstrak: Perkembangan teknologi yang semakin pesat menuntut generasi muda juga lebih kreatif dan inovatif untuk mengembangkan dirinya. Seperti telah kita ketahui bahwa saat ini persediaan bahan bakar fosil semakin menipis, dan tentu saja ini menjadi tantangan tersendiri bagi generasi muda. Menghadapi hal ini, maka saat ini banyak dikembangkan kendaraan bermotor berbasis listrik yang harapan kedepannya nanti akan mampu berkembang dan pemanfaatannya lebih luas. Salah satu yang menjadi pilihan adalah motor listrik. Guna mendukung perkembangan kendaraan listrik, Program Studi Pendidikan Teknik Elektro Universitas PGRI Madiun, mencoba mengembangkan motor listrik berbasis BLDC motor atau Brushless DC Motor . Dimana pemahaman konsep terlebih dahulu ditekankan agar mahasiswa lebih memahami sistem kerja dari BLDC motor ini. Melalui pembelajaran berbasis proyek, mahasiswa dapat lebih cepat memahami tentan sistem kerja BLDC motor . Hasil penelitian menunjukkan adanya peningkatan pemahaman konsep mengenai sistem kerja dari BLDC MOTOR . Peningkatan memiliki nilai N-Gain medium. Dari hasil tersebut maka dapat disimpulkan bahwa melalui pembelajaran berbasis proyek untuk BLDC motor mampu meningkatkan pemahaman konsep mengenai sistem kerja BLDC motor.